Drawbacks of Long-Acting Intramuscular Antipsychotic Injections - V. Seeman, Mary (Journal of Clinical and Practical Nursing, 2017)
Second-generation antipsychotics have relatively recently become available in long-acting intramuscular formulations (LAIs) and have been receiving a substantial amount of pharmaceutical industry promotion on the grounds that they improve treatment adherence in patients with psychotic illness. LAIs do have some drawbacks, however, which is the topic area covered by this review. A Global Scholar search of the nursing and medical literature reveals several factors that can negatively impinge on the clinical efficacy of LAIs: 1. The extent of training of injection personnel 2. The quality of surveillance of patient symptoms and side effects 3. The skilled use of the full range of injection techniques 4. The extent of drug accumulation over time 5. The potential loss of drug dose flexibility 6. The impact of exercise and temperature on drug distribution 7. The burden of the medication routine and the social burdens of LAIs 8. The safety of LAIs during pregnancy 9. The perceived coerciveness of LAIs 10. Issues of overdose and polypharmacy 11. Issues of cost 12. The important issue of responsibility for self-management of illness. Although the evidence is clinical and anecdotal, LAIs appear to work well for many patients, but their drawbacks are not negligible. Clinicians need to weigh individual risks and benefits when making treatment decisions.
Keywords: Antipsychotics; Depot; Injections; Intramuscular; Long-acting